ACCELERATING MODEL DEVELOPMENT IN FINANCE: A MODERN FRAMEWORK FOR ENHANCED EFFICIENCY AND PERFORMANCE - Pavan Rupanguntla, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
A modernized framework for accelerating model development in consumer finance addresses key challenges in traditional approaches by leveraging machine learning algorithms, unified data processing, continuous performance evaluation, and dynamic variable exploration. The framework enhances model development efficiency and effectiveness while maintaining regulatory compliance. Implementation at major financial institutions demonstrates significant reductions in development time and costs while improving performance and risk management capabilities. The documented results from a leading consumer finance institution highlight practical benefits and strategic advantages gained through adopting this innovative approach to model development and validation.